Consumer engagement with football brands on social media : what drives consumers to engage with FC Porto on social media? - Ferreira, Frederico Correia (2019)
Facebook, and recently Instagram, are established marketing tools that allow brands to connect and engage with their consumers at a level far beyond the reach of traditional offline marketing. To fine tune their messages on social media, brands need to know their consumers’ motivations to engage. However, this information is especially difficult to assemble for sports brands, and, particularly, for football brands. Football consumers are extremely passionate and unpredictable, and, moreover, the core product is highly intangible. Hence, the goal of our research is to understand what are the motivations for FC Porto fans to engage with the brand on Facebook and Instagram. To reach that goal, an online survey was performed and 250 questionnaires were collected. Since the social media strategy followed by FC Porto is developed around the games, we performed a cluster analysis dividing fans into two groups: game-enthusiastic and game-detached. We used Linear Regressions to measure the motivations before and after the clusters analysis. Prior to the clusters analysis, evidence shows the motivations that significantly trigger consumer engagement the most on Facebook are social influence, entertainment, search for information and reward. On Instagram, the most influential motivations are entertainment and reward. After the clusters analysis, evidence shows that consumer engagement on Facebook for cluster nº1 is triggered by entertainment and social influence, and for cluster nº2 is triggered by entertainment, social influence and reward. Regarding Instagram, cluster nº1 is triggered by entertainment, social influence and reward, and cluster nº2 is triggered by entertainment and reward.